Jewish Liberation Theology and its perspectives among Jewish religious leaders on the Israeli-Palestinian conflict - Triandi, Benny; Mulyana, Mulyana (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study explores the theological perspectives of Jewish religious leaders on the Israel–Palestine conflict, with a particular focus on Jewish Liberation Theology. Employing a qualitative approach through literature review and in-depth interviews with nine rabbis representing three theological strands—Religious Zionism, Moderate Judaism, and Liberation Theology—this research examines how the Jewish collective historical experience, particularly the Shoah and diaspora, has shaped differing interpretations of justice, power, and interfaith relations. The analysis adopts a contextual hermeneutic paradigm that integrates textual interpretations of the Torah, Talmud, and prophetic literature with ethical reflection on structural oppression and political violence. The findings reveal that Jewish Liberation Theology constructs a narrative of universal solidarity, rejecting exclusivist claims to sacred land and advocating for the rights of Palestinians as a moral imperative rooted in Torah ethics. In contrast, Religious Zionist theology affirms the establishment of the State of Israel as a fulfillment of divine prophecy and upholds Jewish ethno-religious sovereignty. Meanwhile, Moderate Jewish theology seeks a balance between pluralism, democracy, and religious tradition. The study concludes that these theological divergences have significant implications for the political and ethical orientations of Jewish communities both in Israel and the diaspora. The research contributes to the field of religious studies by offering a new typological mapping of Jewish theological responses to political conflict and demonstrating how religious belief can function both as a source of domination and as a liberating moral force.